Implementation of the Contextual Teaching and Learning (CTL) Approach Through Student-Produced Video Learning Materials at SMPN 1 Tanjunganom Nganjuk - Dewi Mahbubah; Ansori, Miksan (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2022)
This research aims to explore the implementation of the Contextual Teaching and Learning (CTL) approach through the production of video lessons by seventh-grade students at SMPN 1 Tanjunganom, Nganjuk Regency. A qualitative research method was employed, utilizing interviews, observations, and document analysis. The findings indicate that student learning outcomes improved following the implementation of CTL-based video production. Furthermore, the study observed a significant increase in student engagement and enthusiasm during the learning process. This heightened interest is attributed to the hands-on experience of producing short educational videos. The incorporation of video production in learning activities also suggests a potential enhancement of students' higher-order thinking skills.